Pemetaan dan Evaluasi Kesesuaian Curah Hujan untuk Tanaman Kelapa Sawit di Kecamatan Bintang Bayu Kabupaten Serdang Bedagai Provinsi Sumatera Utara - Sakiah, Sakiah; Febrianto, Eka Bobby; Sudrajat, Ayi; Siregar, Albert Kristian (Politeknik Negeri Lampung, 2021)
Climate is one of the factors that influence the growth, and production of palm oil, one of the most important climate elements is rain. Rain is the main source of water in meeting the needs of palm oil trees. This research aimed to map the climate type of Bintang Bayu region and to determine the trend of rainfall in 10 years (2010-2019) in Bintang Bayu Sub-district, Serdang Bedagai District, Sumatera Utara Province. This research used Geographical Information Systems (GIS) and descriptive-analytical methods. Rainfall data derived from satellite imagery (Data Chips-2.0, UCSB) obtained from the Meteorology and Geophysics Agency (BMKG) Stasiun Klimatologi region of Deli Serdang which was used as the basis for determining dry and wet months based on Schmidt-Ferguson. Evaluation of rainfall suitability was carried out by comparing the annual rainfall observation data with the Palm Oil Land Suitability Criteria based on the Indonesian Center for Agricultural Land Resources Research and Development. The results showed that Bintang Bayu Sub-district had climate type A (tropical rain forest), in which, in the area with climate type A was suitable for palm oil plants. Based on the distribution of annual rainfall, there were two distributions of rain, that were 2,500-3,000 mm.year-1 and 3,000-3,500 mm.year-1, there were no areas with an annual rain distribution of 2,000-2,500 mm.year-1, thus the Bintang Bayu region is included in the S2 class. In ten years, there was an increase in rainfall in January, May, July, and October while in other months there was a decrease in rainfall.